2019
DOI: 10.1158/0008-5472.can-19-1816
|View full text |Cite
|
Sign up to set email alerts
|

Serine-Glycine-One-Carbon Metabolism: The Hidden Achilles Heel of MYCN-Amplified Neuroblastoma?

Abstract: In this issue of Cancer Research, Xia and colleagues show that MYC-induced metabolic reprograming results in dependency on the serine-glycine-one-carbon (SGOC) metabolic pathway in neuroblastoma. This occurs through MYCN and ATF4 activation of the SGOC biosynthetic pathway in MYCN-amplified cells. Furthermore, inhibition of de novo serine synthesis generates metabolic stress in MYCN-amplified neuroblastoma cells, causing cellcycle arrest and autophagy. Together, these data suggest that the SGOC pathway is an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Multiple mechanisms mediated by oncogenes, such as exosomal-microRNAs and cell signaling pathways, were identified to promote CDDP-insensitivity in neuroblastoma [ 10 , 18 , 19 , 20 ]. The oncogenes, including v-myc avian myelocytomatosis viral oncogene neuroblastoma derived homolog (MYCN) and Hypoxia-inducible factor (HIF)-1∝, were shown to regulate metabolism and mediate CDDP-resistance in neuroblastoma [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple mechanisms mediated by oncogenes, such as exosomal-microRNAs and cell signaling pathways, were identified to promote CDDP-insensitivity in neuroblastoma [ 10 , 18 , 19 , 20 ]. The oncogenes, including v-myc avian myelocytomatosis viral oncogene neuroblastoma derived homolog (MYCN) and Hypoxia-inducible factor (HIF)-1∝, were shown to regulate metabolism and mediate CDDP-resistance in neuroblastoma [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that, because of MYCN-mediated metabolic reprogramming, MYCN -amplified tumor cells are increasingly dependent on key metabolic pathways for proliferation and survival, such as the serine–glycine–one-carbon metabolic network [ 9 , 10 ]. Exploiting this dependency is a promising therapeutic strategy against MYCN -amplified tumors [ 9 11 ]. Our current study provides further evidence in support of this strategy by identifying DHODH as a promising therapeutic target in MYCN -amplified neuroblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, this metabolic reprogramming, while essential to sustain cell proliferation, renders tumor cells dependent on the SGOC pathway. As a result, MYCN -amplified neuroblastoma cells are highly sensitive to inhibitors that block this metabolic pathway, suggesting that targeting SGOC metabolism may provide selective therapeutic benefits for patients with MYCN -amplified cancers [ 10 , 11 ]. We reasoned that a comprehensive profiling of MYCN-activated metabolic pathways may identify new avenues that could be exploited therapeutically.…”
Section: Introductionmentioning
confidence: 99%
“…While numerous studies have demonstrated a key role of MYCN in NB and GBM metabolism (176)(177)(178)(179)(180), its metabolic function in medulloblastoma still remains elusive. It is likely that in these tumours, as in other cancers, MYCN reconfigures metabolism to favour aerobic glycolysis and a dependency on the serineglycine-one-carbon (SGOC) to generate metabolic products starting from serine and glycine amino acids (181).…”
Section: Future Areas Of Research For Innovative Therapies Mycn-driven Cancer Metabolismmentioning
confidence: 99%